2023
DOI: 10.1111/jcpe.13764
|View full text |Cite
|
Sign up to set email alerts
|

Individual “alveolar phenotype” limits dimensions of lateral bone augmentation

Abstract: Aim Alveolar ridge resorption following tooth extraction often renders a lateral bone augmentation inevitable. Some patients, however, suffer from severe early (during graft healing, Eres) and/or late (during follow‐up, Lres) graft resorption. We explored the hypothesis that the “individual phenotypic dimensions” may partially explain the degree of such resorptions. Materials and Methods Patients who underwent a guided bone regeneration (GBR) procedure were screened for inclusion according to the following cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Interestingly, data suggested that deeper defects with narrower baseline radiographic defect angles (DAs) exhibit more favorable reconstructive outcomes 14 . This is consistent with data derived from guided bone regeneration in alveolar deficiencies, where individual phenotypic dimensions and the buccal DA are key to understand the predictability of regenerative procedures 15,16 . In the arena of reconstructive therapy for the management of peri‐implantitis, however, the influence of the DA upon the outcomes is yet unexplored.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Interestingly, data suggested that deeper defects with narrower baseline radiographic defect angles (DAs) exhibit more favorable reconstructive outcomes 14 . This is consistent with data derived from guided bone regeneration in alveolar deficiencies, where individual phenotypic dimensions and the buccal DA are key to understand the predictability of regenerative procedures 15,16 . In the arena of reconstructive therapy for the management of peri‐implantitis, however, the influence of the DA upon the outcomes is yet unexplored.…”
Section: Introductionsupporting
confidence: 59%
“…In fact, it was found that in cases of a crest angulation of <150°, the horizontal bone gain was ∼4, whereas in scenarios presenting crest angulation >150°, the gain was ∼3 mm lesser. More recently, Quirynen and colleagues 16 demonstrated the existence of individual alveolar phenotypes to predict horizontal ridge augmentation using 3‐dimensional virtual reconstruction and superimposition of CBCT data, with the contralateral ridge dimensions as reference. One possible explanation for this finding is the stability of the coagulum and the material that provides the barrier membrane in a contained defect in contrast to a flat architecture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Interestingly, a recent study indicated that the "individual phenotypical dimension" (which represents the natural alveolar crest contour before tooth loss) may be a predictor of how much buccally one can regenerate bone when applying the GBR concept. 75 Hence, over-augmentation beyond the boundary line of the bony envelope may not be a successful strategy.…”
Section: The Influence Of Biomaterials On Peri-implant Bone Levelsmentioning
confidence: 99%
“…It is worth noting that bone resorption after LRA can vary based on the patient's individual phenotype dimensions, as observed in a study comparing the healthy contra-lateral site of the LRA. 47,111 This highlights the importance of considering over-engineering during LRA. 47 • Therefore, it is critical to follow a workflow that ensures predictable long-term biological and esthetic outcomes in all scenarios.…”
Section: Ridg E Width (L Ater Al Ridg E Deficien C Y )mentioning
confidence: 99%